Adjusting to trade policy: Evidence from U.S. antidumping duties on Vietnamese catfish - Brambilla, Irene (2012)
In 2003, after claims of dumping, the United States imposed heavy tariffs on Vietnamese catfish, which led to a collapse of imports. We use panel data to explore household responses in the catfish-producing Mekong delta between 2002 and 2004 and find that income growth was significantly slower among households relatively more involved in catfish farming in 2002. This is explained by a relative decline in both catfish income and revenues from other miscellaneous farm activities. Labor supply did not adjust, most likely because of off-farm employment limitations. Households more exposed to the shock reduced the share of investment assigned to catfish while substituting into agriculture.